A Possible Mechanism of Zika Virus Associated Microcephaly: Imperative Role of Retinoic Acid Response Element (RARE) Consensus Sequence Repeats in the Viral Genome - Kumar, Ashutosh; Singh, Himanshu N.; Pareek, Vikas; Raza, Khursheed; Dantham, Subrahamanyam; Kumar, Pavan; Mochan, Sankat; Faiq, Muneeb A. (Frontiers in Human Neuroscience, 2016)
Owing to the reports of microcephaly as a consistent outcome in the fetuses of pregnant women infected with ZIKV in Brazil, Zika virus (ZIKV)—microcephaly etiomechanistic relationship has recently been implicated. Researchers, however, are still struggling to establish an embryological basis for this interesting causal handcuff. The present study reveals robust evidence in favor of a plausible ZIKV-microcephaly cause-effect liaison. The rationale is based on: (1) sequence homology between ZIKV genome and the response element of an early neural tube developmental marker “retinoic acid” in human DNA and (2) comprehensive similarities between the details of brain defects in ZIKV-microcephaly and retinoic acid embryopathy. Retinoic acid is considered as the earliest factor for regulating anteroposterior axis of neural tube and positioning of structures in developing brain through retinoic acid response elements (RARE) consensus sequence (5′–AGGTCA–3′) in promoter regions of retinoic acid-dependent genes. We screened genomic sequences of already reported virulent ZIKV strains (including those linked to microcephaly) and other viruses available in National Institute of Health genetic sequence database (GenBank) for the RARE consensus repeats and obtained results strongly bolstering our hypothesis that ZIKV strains associated with microcephaly may act through precipitation of dysregulation in retinoic acid-dependent genes by introducing extra stretches of RARE consensus sequence repeats in the genome of developing brain cells. Additional support to our hypothesis comes from our findings that screening of other viruses for RARE consensus sequence repeats is positive only for those known to display neurotropism and cause fetal brain defects (for which maternal-fetal transmission during developing stage may be required). The numbers of RARE sequence repeats appeared to match with the virulence of screened positive viruses. Although, bioinformatic evidence and embryological features are in favor of our hypothesis, additional studies including animal models are warranted to validate our proposition. Such studies are likely to unfold ZIKV-microcephaly association and may help in devising methods to combat it.